Pericardial fat and myocardial perfusion in asymptomatic adults from the Multi-Ethnic Study of Atherosclerosis. - Tina E Brinkley; Michael Jerosch-Herold; Aaron R Folsom; J Jeffrey Carr; W Gregory Hundley; Matthew A Allison; David A Bluemke; Gregory L Burke; Moyses Szklo; Jingzhong Ding (PLoS ONE)
Background Pericardial fat has adverse effects on the surrounding vasculature. Previous studies suggest that pericardial fat may contribute to myocardial ischemia in symptomatic individuals. However, it is unknown if pericardial fat has similar effects in asymptomatic individuals. Methods We determined the association between pericardial fat and myocardial blood flow (MBF) in 214 adults with no prior history of cardiovascular disease from the Minnesota field center of the Multi-Ethnic Study of Atherosclerosis (43% female, 56% Caucasian, 44% Hispanic). Pericardial fat volume was measured by computed tomography. MBF was measured by MRI at rest and during adenosine-induced hyperemia. Myocardial perfusion reserve (PR) was calculated as the ratio of hyperemic to resting MBF. Results Gender-stratified analyses revealed significant differences between men and women including less pericardial fat (71.9±31.3 vs. 105.2±57.5 cm(3), p<0.0001) and higher resting MBF (1.12±0.23 vs. 0.93±0.19 ml/min/g, p<0.0001), hyperemic MBF (3.49±0.76 vs. 2.65±0.72 ml/min/g, p<0.0001), and PR (3.19±0.78 vs. 2.93±0.89, p = 0.03) in women. Correlations between pericardial fat and clinical and hemodynamic variables were stronger in women. In women only (p = 0.01 for gender interaction) higher pericardial fat was associated with higher resting MBF (p = 0.008). However, this association was attenuated after accounting for body mass index or rate-pressure product. There were no significant associations between pericardial fat and hyperemic MBF or PR after multivariate adjustment in either gender. In logistic regression analyses there was also no association between impaired coronary vasoreactivity, defined as having a PR <2.5, and pericardial fat in men (OR, 1.18; 95% CI, 0.82-1.70) or women (OR, 1.11; 95% CI, 0.68-1.82). Conclusions Our data fail to support an independent association between pericardial fat and myocardial perfusion in adults without symptomatic cardiovascular disease. Nevertheless, these findings highlight potentially important differences between asymptomatic and symptomatic individuals with respect to the underlying subclinical disease burden.